EFFECTS OF BLUE LED ON VENOUS ULCER HEALING IN DIABETICS - Ferreira Oliveira, Tatiana (2023)
Ulcers in patients with Diabetes Mellitus are frequent and considered one of the most relevant complications during the clinical course of the disease. To analyze the application of blue light-emitting diode (LED) in tissue repair of venous ulcer of the lower limb. It consisted of the application of blue LED, with a wavelength around 680 THz and 620 THz at the wound site, for 10 minutes, 2 times a week, for 5 weeks. Assessment tools for pain and neuropathic symptoms, sensitivity tests, daily photographic record, measurement of ulcer size and wound closure time index were used. Improvement in tissue repair of wounds was observed, reaching total closure on both sides and reduction of referred pain intensity. LED as a curative treatment of chronic diabetic ulcers showed effectiveness in the rate of total wound closure and improvement of neuropathic symptoms.